Micro and macro perspectives in analysis: Discussions about the applicability of the concept of scale in research on teacher education - Shigunov Neto, Alexandre; Silva, André Coelho da (Revista Hipótese, 2022)
This study intends to carry out initial discussions on the possibilities of using the concept of scale in educational research, analyzing, in particular, the limitations and potentialities of the microsocial and macrosocial perspectives in teacher education. Current studies indicate that educational research is used from one perspective at the expense of another. It is believed that despite the various challenges in trying to articulate the micro and macrosocial perspectives in the same research problem, the use of the two perspectives together tends to broaden the understanding of the studied problem.